Relationships between maintenance of sinus rhythm and clinical outcomes in patients with heart failure with preserved ejection fraction and atrial fibrillation. Issue 3 (September 2019) - Machino-Ohtsuka, Tomoko; Seo, Yoshihiro; Ishizu, Tomoko; Yamamoto, Masayoshi; Hamada-Harimura, Yoshie; Machino, Takeshi; Yamasaki, Hiro; Sekiguchi, Yukio; Nogami, Akihiko; Aonuma, Kazutaka; Ieda, Masaki
Highlights: Atrial fibrillation (AF) is a potent and independent predictor for deterioration of heart failure with preserved ejection fraction (HFpEF). Maintenance of sinus rhythm was associated with a lower rate of cardiovascular events. Maintenance of sinus rhythm was not associated with all-cause mortality. Randomized trials are needed to verify the impact of rhythm control for AF in HFpEF. Abstract: Background: Although atrial fibrillation (AF) is associated with exacerbation of heart failure with preserved ejection fraction (HFpEF), the relationships between maintenance of sinus rhythm (SR) and clinical outcomes in HFpEF is unknown. We investigated whether maintenance of SR was associated with better prognosis compared with rate control in patients with concomitant HFpEF and AF. Methods: We conducted a retrospective, observational study of 283 patients with HFpEF and AF. Of these, 107 patients achieved maintenance of SR by catheter ablation and/or antiarrhythmic drugs (rhythm control) and 176 were treated with rate control. The propensity score (PS) for each patient in both treatment groups was estimated, resulting in selectively matched subgroups of 79 patients each. All-cause death and a composite of cardiovascular death or hospitalization for heart failure (HF) were analyzed. Results: During a median follow-up period of 24 months, all-cause mortality was comparable between groups; however, maintenance of SR was significantly associated with a lower incidence of the composite endpoint [adjusted hazard ratio (HR), 0.30; 95% confidence interval, 0.18–0.98; p  = 0.04] in the PS-matched cohort. The PS-adjusted multivariable analysis based on 283 pre-matched patients also revealed that rhythm control was associated with a lower rate of the composite endpoint (adjusted HR, 0.27; 95% CI, 0.12–0.61; p  = 0.002). Subgroup analyses suggested that rhythm control was consistently related to the composite endpoint across a wide spectrum of HFpEF patients. Conclusions: Maintenance of SR was associated with a lower risk of composite of cardiovascular death or hospitalization for HF in patients with HFpEF and AF. A randomized trial is necessary to confirm this result.